Biochar / carbon nanotube / myristic acid composite phase change material as well as preparation method and application thereof

By performing alkali modification treatment on biochar and adding carbon nanotubes and myristic acid to form a composite phase change material, the problems of low thermal conductivity and poor light absorption capacity of existing phase change materials are solved, and efficient photothermal conversion and stable thermal energy storage are achieved.

CN119859509APending Publication Date: 2025-04-22ZHEJIANG UNIV OF SCI & TECH

Patent Information

Application Number
CN202510078901.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Existing phase change materials have problems such as easy leakage, low thermal conductivity and poor light absorption in the fields of thermal energy storage and conversion, which limits their application.

Method used

Biochar is treated by alkali modification, and carbon nanotubes and myristic acid are added on the basis to form a biochar/carbon nanotube/myristic acid composite phase change material, improving its thermal conductivity and light absorption capacity.

Benefits of technology

It significantly improves the thermal conductivity and light absorption performance of composite phase change materials, improves the photothermal conversion efficiency, enhances the leakage resistance, and improves the stability and performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859509A_ABST
    Figure CN119859509A_ABST
Patent Text Reader

Abstract

The invention discloses a biochar / carbon nanotube / myristic acid composite phase change material as well as a preparation method and application thereof, and belongs to the technical field of heat storage. The meat biochar / carbon nanotube / myristic acid composite phase change material is prepared by adopting a vacuum impregnation method. The original biochar is modified by KOH, so that the specific surface area and pore volume of a sample are increased, the specific surface area of the modified KBC3 reaches 813.56 m < 2 > / g, and the loading capacity of the KOH modified biochar on MA is increased to 63%. The result shows that the MA sample is successfully loaded into the porous material, and the structure is kept intact. In order to further improve the loading rate and the leakage resistance of the phase change material, carbon nanotubes are doped in the KBC / MA phase change material, and when the loading rate of MA is improved to 75%, KBC1.5 / MA severely leaks in a shape stability performance experiment, and the mass loss rate reaches 8.5%. And KBC1.5 / CNT1 / MA only has little leakage in the thermal stability test process, so that the leakage resistance of the composite phase change material is greatly enhanced. Through BC modification and CNTs introduction, the heat conduction capability and the photothermal conversion capability of the composite PCMs are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of heat storage, and in particular relates to a biochar / carbon nanotube / myristic acid composite phase change material and a preparation method and application thereof. Background Art

[0002] The efficient development of phase change materials plays an important role in the photothermal conversion and storage of solar energy. As an abundant and environmentally friendly renewable energy, solar energy has significant environmental benefits, but its intermittent and unstable nature limits its widespread application in the field of thermal energy storage and conversion. Therefore, the development of efficient thermal energy storage materials to maximize the use of solar energy has become an important topic in the field of materials science and engineering.

[0003] Phase change materials (PCMs) can efficiently absorb and release a large amount of latent heat within a small temperature fluctuation range, effectively balancing the acquisition and utilization of solar energy. However, single phase change materials have problems such as easy leakage, low thermal conductivity and poor light absorption capacity, which limit their application. At present, encapsulating phase change materials in porous media has become an effective method to prevent leakage of solid-liquid phase change materials. The tiny pores inside the porous medium can disperse the phase change material into tiny particles, and use the capillary effect to improve storage reliability and avoid liquid leakage. Biochar, as an encapsulation carrier of phase change materials, has a high specific surface area, porous structure and rich oxygen-containing functional groups, showing ideal adsorption capacity. However, the pore structure of the original biochar is not well developed, which limits the improvement of the performance of composite phase change materials.

[0004] Based on the above reasons, this application is filed. Summary of the invention

[0005] Based on the above reasons, in view of the problems or defects in the prior art, the purpose of the present invention is to provide a biochar / carbon nanotube / myristic acid composite phase change material and its preparation method and application, to solve or at least partially solve the above technical defects in the prior art: the present invention can significantly improve the surface structure characteristics of biochar through alkali modification treatment. In addition, improving the thermal conductivity and light absorption capacity of the composite phase change material is crucial for the photothermal conversion of solar energy. The addition of carbon nanotubes of the present invention can not only improve the thermal conductivity of the composite phase change material, but also enhance its light absorption performance, further improving the photothermal conversion efficiency. The present invention only needs to add a small amount of carbon nanotubes of suitable diameter to significantly improve the light absorption performance and loading capacity.

[0006] In order to achieve one of the above purposes of the present invention, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing a biochar / carbon nanotube / myristic acid composite phase change material, the method specifically comprising the following steps:

[0008] (1) Preparation of biochar / myristic acid

[0009] Myristic acid (MA) and anhydrous ethanol are mixed, heated and melted to obtain a liquid phase change material; biochar (BC) is then added to the liquid phase change material according to a ratio and mixed; the obtained mixture is then vacuum impregnated, and after the vacuum impregnation is completed, the biochar / myristic acid (BC / MA) is obtained;

[0010] (2) Preparation of biochar / carbon nanotubes / myristic acid

[0011] Carbon nanotubes (CNTs) are added to molten myristic acid according to a ratio, and then stirred and ultrasonicated under molten conditions to obtain a carbon nanotube / myristic acid (MA / CNTs) mixed solution; KOH-activated biochar (KBC) is then added to the MA / CNTs mixed solution, mixed evenly, and the obtained mixture is vacuum dried to obtain the biochar / carbon nanotube / myristic acid composite phase change material.

[0012] Furthermore, in the above technical solution, the mass ratio of myristic acid to biochar in step (1) is 1:1 to 2:1, preferably 1.8:1.

[0013] Furthermore, in the above technical solution, the specific process of vacuum impregnation in step (1) is as follows: the temperature is 60-70° C. and the time is 2-4 hours.

[0014] Furthermore, in the preferred embodiment of the present invention, the biochar in step (1) is prepared by calcining plant straw at high temperature and then sieving it.

[0015] Furthermore, in the above technical solution, the method for preparing the biochar in step (1) is as follows:

[0016] The dried plant straw is crushed and placed in a tubular furnace, and heated to 500-700° C. for pyrolysis for 1-3 hours under the protection of an inert gas; after the pyrolysis is completed, the obtained product is ground to obtain the biochar.

[0017] Preferably, in the above technical solution, the heating rate is 5-15°C / min.

[0018] Furthermore, in the above technical solution, the mass ratio of the carbon nanotubes to myristic acid in step (2) is 1:10 to 1:30.

[0019] Furthermore, in the above technical solution, the mass ratio of CNTs to KBC in step (2) is 1:9.

[0020] Furthermore, in the above technical solution, the activated biochar in step (2) is prepared by the following method:

[0021] (A) dissolving KOH in deionized water according to a ratio to obtain a KOH solution; then adding plant straw particles to the KOH solution, immersing for 20-30 hours, filtering, and drying to obtain KOH-activated plant straw;

[0022] (B) placing the KOH-activated plant straw in a tubular furnace, heating it to 500-700° C. for pyrolysis for 1-3 hours under the protection of an inert gas; after the pyrolysis is completed, washing the obtained product to neutrality, drying, and grinding to obtain KOH-activated biochar.

[0023] Furthermore, in the above technical solution, the concentration of the KOH solution in step (A) is 100-300 g / L.

[0024] Furthermore, in the above technical solution, in step (A), the mass ratio of KOH to plant straw particles is (1-3):1, preferably 1.5:1.

[0025] The second object of the present invention is to provide a biochar / carbon nanotube / myristic acid composite phase change material prepared by the above method.

[0026] The third object of the present invention is to provide the use of the biochar / carbon nanotube / myristic acid composite phase change material prepared by the above method as a photothermal conversion material.

[0027] The present invention also provides a photothermal conversion material, comprising the biochar / carbon nanotube / myristic acid composite phase change material prepared by the method described above.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The present invention adopts vacuum impregnation method to prepare meat biochar / carbon nanotube / myristic acid composite phase change material. The original biochar is modified by KOH to increase the specific surface area and pore volume of the sample. After modification, the specific surface area of ​​KBC3 reaches 813.56m 2 / g, the loading amount of MA by KOH-modified biochar increased to 63%. Various characterization results show that the MA sample was successfully loaded into the porous material and the structure remained intact. In order to further improve the loading rate and anti-leakage performance of the phase change material, carbon nanotubes were doped into the KBC / MA phase change material. When the loading rate of MA was increased to 75%, KBC1.5 / MA(75) leaked seriously in the shape stability performance experiment, and the mass loss rate reached 8.5%. However, only a small amount of leakage occurred in the thermal stability test of KBC1.5 / CNT1 / MA(75), and the anti-leakage ability of the composite phase change material was greatly enhanced. KBC1.5 / CNT3 / MA(75) has a higher phase change enthalpy value of 143.5J / g and higher long-term durability and stability. The thermal cycle curve after 100 times coincides with the single DSC curve. BC modification and the introduction of CNTs greatly improve the thermal conductivity and photothermal conversion ability of the composite PCMs. The photothermal conversion rate of pure MA and BC / MA(63) is 0. The photothermal conversion rate of KBC1.5 / MA was increased to 58.88%, while that of KBC1.5 / CNT2 / MA(63) was further increased to 76.37%. The addition of a small amount of CNTs has an important influence on the performance improvement of composite PCMs, which is mainly due to the higher thermal conductivity and stronger visible light absorption ability of carbon nanotubes. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 Component composition diagram of three biochar samples BC, KBC1.5 and KBC3 prepared in Example 1 of the present invention and Comparative Example 1 respectively.

[0032] Figure 2 In the figure: (a) and (a′) are SEM images of BC prepared in Example 1; (b) and (b′) are SEM images of KBC1.5 prepared in Example 1; (c and (c′) are SEM images of KBC3 prepared in Comparative Example 1; (d) is a SEM image of the composite phase change material KBC1.5 / MA(63) prepared in Comparative Example 2; (e) is a SEM image of the composite phase change material KBC1.5 / CNT2 / MA(75) prepared in Example 3.

[0033] Figure 3 XRD comparison diagrams of composite phase change materials prepared from pure MA, comparative examples 1-3, and examples 1-4, respectively.

[0034] Figure 4 In the figure: (a) is the DSC curve of pure MA, KBC3 / MA(63), KBC1.5 / MA(63), BC / MA(63), and KBC1.5 / CNT3 / MA(63) prepared in comparative examples 1-3 and example 1 respectively; (b) is the DSC curve of the composite phase change materials KBC1.5 / CNT3 / MA(75), KBC1.5 / CNT2 / MA(75), and KBC1.5 / CNT1 / MA(75) prepared in examples 2-4 respectively; (c) thermal cycle curve.

[0035] Figure 5 In the figure: (a) is the TG curve of pure MA, KBC3 / MA(63), KBC1.5 / MA(63), BC / MA(63), and KBC1.5 / CNT3 / MA(63) prepared by comparative examples 1-3, and example 1, respectively; (b) is the TG curve of the composite phase change materials KBC1.5 / CNT3 / MA(75), KBC1.5 / CNT2 / MA(75), and KBC1.5 / CNT1 / MA(75) prepared by examples 2-4, respectively.

[0036] Figure 6 In the figure: (a) is an infrared thermal imaging image of the instantaneous temperature of the composite phase change materials KBC3 / MA(63), KBC1.5 / MA(63), and KBC1.5 / CNT3 / MA(63) prepared in Comparative Examples 1-2 and Example 1, respectively; (b) is an infrared thermal imaging image of the instantaneous temperature of the composite phase change materials KBC1.5 / CNT3 / MA(75), KBC1.5 / CNT2 / MA(75), and KBC1.5 / CNT1 / MA(75) prepared in Examples 2-4, respectively.

[0037] Figure 7 Comparison charts of leakage tests and mass loss rates of composite phase change materials KBC3 / MA(63), KBC1.5 / MA(63), KBC1.5 / CNT3 / MA(63), KBC1.5 / MA(75), and KBC1.5 / CNT1 / MA(75) prepared from pure MA, comparative examples 1-4, and example 4, respectively.

[0038] Figure 8 Middle: (a) The photothermal conversion curve of the phase change material with a theoretical loading rate of pure MA of 63% (b) The photothermal conversion curve of the phase change material with a theoretical loading rate of MA of 75%. DETAILED DESCRIPTION

[0039] The present invention is further described in detail below through implementation cases. This implementation case is implemented based on the technology of the present invention, and a detailed implementation method and specific operation process are now given to illustrate that the present invention is creative, but the protection scope of the present invention is not limited to the following implementation cases.

[0040] According to the information contained in this application, various changes can be easily made to the precise description of the present invention for those skilled in the art.It should be understood that the scope of the present invention is not limited to defined processes, properties or components, because these embodiments and other descriptions are only for illustrating specific aspects of the present invention.

[0041] In order to better understand the present invention but not to limit the scope of the present invention, all the numbers used in this application to express the amount, percentage, and other numerical values ​​should be understood as modified by the word "about" in all cases. Therefore, unless otherwise specified, the numerical parameters listed in the specification are approximate values, which may be changed according to the different ideal properties attempted to be obtained. Each numerical parameter should at least be regarded as obtained based on the reported significant figures and by conventional rounding methods.

[0042] The equipment and raw materials used in the present invention can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.

[0043] The corn stalks used in the following embodiments of the present invention were purchased from a corn farm in Jiangsu, anhydrous ethanol and myristic acid (MA) were purchased from Sinopharm Chemical Reagent Co., Ltd., KOH was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., and CNTs were purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., where the length of the CNTs was 0.5-2um, the inner diameter was 5-15nm, and the outer diameters were 5-15nm, 10-20nm, and 30-50nm, respectively, and were named CNT1, CNT2, and CNT3, respectively.

[0044] Example 1

[0045] The present embodiment provides a method for preparing a biochar / carbon nanotube / myristic acid composite phase change material, the method specifically comprising the following steps:

[0046] (1) Preparation of biochar

[0047] High-temperature carbonized corn straw biochar BC: First, the dried corn straw was crushed into 10 mesh and placed in a crucible, and then placed in a tubular furnace. Under the protection of pure nitrogen, the corn straw was heated from room temperature to 600°C for pyrolysis at a heating rate of 10°C / min, kept warm for 2h, and finally ground through a 100-mesh sieve to obtain the original corn straw biochar, named BC.

[0048] (2) KOH activated biochar: First, weigh 15 g of KOH and place it in 100 ml of deionized water. After stirring to dissolve, add 10 g of dry corn straw particles and soak for 24 h. Filter to remove excess liquid and dry in a drying oven at 110 °C for 8 h. Repeat the same carbonization process in step (1) above for the sample pretreated with KOH. The obtained biochar is washed with deionized water several times until the pH value of the filtrate is close to neutral. Dry at 110 °C and grind through a 100-mesh sieve to obtain KOH activated biochar, which is recorded as KBC1.5.

[0049] (3) Preparation of biochar-based composite phase change materials

[0050] (3.1) Biochar / myristic acid preparation

[0051] Vacuum impregnation technology was used to impregnate myristic acid into the biochar pores to prepare biochar / nutmeg composite materials. 1.1g of phase change material myristic acid was weighed into a small beaker, 10ml of anhydrous ethanol was added, and the liquid phase change material was obtained by heating in a water bath. Then 0.6g of biochar powder was added to the small beaker and stirred with a glass rod to mix it evenly. Finally, the mixture was placed in a 65℃ vacuum drying oven, evacuated and kept warm for 3 hours. The negative pressure generated by vacuuming was used to fully load the phase change material into the pores of the biochar. After the vacuum impregnation was completed, the solid product was placed on the surface of a weighing paper to absorb the excess phase change material, and the biochar-shaped composite PCMs was obtained, which was made into a sheet with a diameter of 2cm and a thickness of 2.8mm using a tablet press.

[0052] (3.2) Biochar / carbon nanotubes / myristic acid preparation

[0053] First, add 0.05g of CNT3 nanoparticles to 0.9g of molten MA, stir magnetically for half an hour, and then perform ultrasonic oscillation for 60 minutes. During this period, the temperature of the sample must be kept above the melting point of myristic acid. Then add 0.45g of the KBC1.5 to the above MA / CNTs mixed solution and stir with a glass rod to mix it evenly. Then place it in a 65°C vacuum drying oven, evacuate and keep warm for 3 hours. After the vacuum impregnation is completed, place the solid product on the surface of weighing paper to absorb the excess phase change material to prepare the biochar / carbon nanotube / myristic acid composite phase change material, recorded as KBC1.5 / CNT3 / MA(63), wherein the mass ratio of KBC1.5 to CNT3 is 9:1, and MA accounts for 63% of the total mass of the sample.

[0054] Example 2

[0055] A biochar / carbon nanotube / myristic acid composite phase change material of this embodiment

[0056] The preparation method of KBC1.5 / CNT3 / MA(75) is basically the same as that in Example 1, the only difference is that the amount of MA used in step 3.2 of this example is 1.5 g, that is, the theoretical loading rate of myristic acid is 75%, and the other processes and parameters are the same.

[0057] Example 3

[0058] A biochar / carbon nanotube / myristic acid composite phase change material of this embodiment

[0059] The preparation method of KBC1.5 / CNT2 / MA(75) is basically the same as that in Example 2, except that CNT2 nanoparticles are used in step 3.2 of this example, and other processes and parameters are the same.

[0060] Example 4

[0061] A biochar / carbon nanotube / myristic acid composite phase change material of this embodiment

[0062] The preparation method of KBC1.5 / CNT1 / MA(75) is basically the same as that in Example 2, except that CNT1 nanoparticles are used in step 3.2 of this example, and other processes and parameters are the same.

[0063] Comparative Example 1

[0064] The preparation method of a biochar / myristic acid composite phase change material KBC3 / MA (63) in this comparative example is basically the same as that in Example 1, except that:

[0065] (1) In step (2) of this comparative example, in the KOH activated biochar KBC, the amount of KOH used was 15 g, the amount of deionized water used was 50 mL, and the amount of dried corn straw particles used was 5 g, that is, m(KOH) / (corn straw)=3, and the other processes were the same, so the KOH activated biochar prepared in this example was recorded as KBC3;

[0066] (2) This comparative example does not use raw material carbon nanotubes, and other processes and parameters are the same.

[0067] Comparative Example 2

[0068] The preparation method of a biochar / myristic acid composite phase change material KBC1.5 / MA(63) in this comparative example is basically the same as that in comparative example 1, the difference is that in step (2) of KOH activation of biochar KBC in this comparative example, the amount of KOH used is 15g, and the amount of dry corn straw particles used is 10g, that is, m(KOH) / (corn straw)=1.5, and the other processes are the same.

[0069] Comparative Example 3

[0070] The preparation method of a composite phase change material BC / MA (63) in this comparative example is basically the same as that in comparative example 1, except that KOH is not used to modify BC in this comparative example, and other processes and parameters are the same.

[0071] Comparative Example 4

[0072] The preparation method of a composite phase change material KBC1.5 / MA (75) in this comparative example is basically the same as that in comparative example 2, except that the amount of MA used in step 3.2 of this comparative example is 1.5 g, and other processes and parameters are the same.

[0073] Results and Discussion:

[0074] (I) Biochar composition

[0075] Three biochar samples were prepared in the present invention, namely BC, KBC1.5 and KBC3.

[0076] The compositions of the three biochar samples are as follows: Figure 1 As shown. Since acid washing was not used to remove ash from biomass in the experiment, the carbon content in BC biochar is only 47.851%, and the other components are ash. The largest proportion of BC ash is SiO2, because the original corn straw BC has a high content of SiO2, followed by K2O, P2O5, CaO, and SO3. There are also many oxides with a content of less than 0.1%. After KOH treatment, the content of SiO2 in the ash is reduced to about 50%. During the roasting process, KOH reacts with SiO2, resulting in a decrease in the SiO2 content. The content of CaO increases accordingly. The content of CaO in the ash of KBC1.5 and KBC3 is 16.998% and 9.360%, respectively, and the contents of other oxides have also increased.

[0077] (II) Sample microstructure

[0078] Figure 2 The SEM images of biochar and composite phase change materials prepared with different alkali-carbon ratios are shown in Figure 2. Figure 1 As shown in (a)-(c), the surface of unmodified BC is very smooth and mainly composed of large pores, with sparse pores and almost no micropores. The surface of modified biochar is rough, and with the increase of alkali-to-carbon ratio, the proportion of small pores on the surface also increases, and the arrangement becomes more dense. It is confirmed that the etching effect of KOH and the reaction of alkali with the functional groups on the surface of biochar have an effect on the pore structure and surface morphology of biochar. In addition, by further magnifying the scanning electron microscope of biochar Figure 2 a'-c' shows that as the alkali-carbon ratio increases, the pore structure of biochar becomes richer, and the pore density and the number of connected pores continue to increase. The SEM results show that KOH modification significantly improves the surface morphology and pore structure of biochar. Figure 2(d) and (e) KBC1.5 / MA(63) and KBC1.5 / CNT2 / MA(75) have relatively smooth surface morphologies, while the latter can clearly observe many disorderly distributed carbon nanotube fibers on the surface. At the same time, the pores of KBC1.5 are full of MA, indicating that MA has been successfully impregnated into the pore structure of KBC1.5.

[0079] In addition, the surface area and pore structure of biochar prepared under direct high-temperature carbonization and KOH activation conditions are compared (Table 1). It can be seen that the specific surface area and total pore volume of biochar directly carbonized at high temperature without KOH modification are slightly lower, and increase several times after KOH modification. The specific surface area of ​​KBC1.5 is 340.41m 2 / g, and the total pore volume is about 0.22cm 3 / g, the specific surface area of ​​KBC3 is 813.56m 2 / g and 0.53m 2 / g. The average pore size shows an opposite trend to the specific surface area and pore volume. The average pore size of BC is 14.26nm, which is about twice that of KBC3 (7.17nm). The average pore size of KBC1.5 is between the two at 9.25nm. This is because the larger the specific surface area, the more micropores the biochar has. The larger the proportion of micropores in the biochar pores, the smaller the average pore size of the biochar. Therefore, it can be considered that different alkali-to-carbon ratios have a very obvious effect on the pore size of biochar.

[0080] Table 1 Comparison of surface area and pore structure of biochar prepared under different activation conditions

[0081]

[0082] (III) Structural characterization of samples

[0083] The crystallinity properties of pure MA and the composite phase change materials prepared in Examples 1-4 and Comparative Examples 1-3 were characterized by XRD. Figure 3As shown, obvious diffraction peaks appear at 2θ of 21.6° and 24.2°, corresponding to the characteristic peaks of pure MA crystals. The composite phase change material also shows obvious diffraction peaks at 2θ of 21.6° and 24.2°, both corresponding to the characteristic peaks of pure MA crystals, indicating that the MA crystal structure in the composite phase change material prepared by the present invention has not changed. The diffraction peak of the composite phase change material BC / MA (63) prepared in Comparative Example 3 at 24.2° is weaker, while the diffraction peak of the composite phase change material KBC / CNT / MA (75) prepared in Examples 2-4 at 24.2° is stronger. This may be because the MA loading rate in KBC / CNT / MA is higher and the structure remains intact. It can be clearly observed in the figure that a new diffraction peak appears at 21.6° in the composite phase change material. The diffraction peak is high and sharp, covering the diffraction peak of the original MA at 21.6°. This is mainly attributed to the diffraction peak of SiO2. SiO2 comes from the biochar itself. Figure 1 It can be seen that there is a high content of SiO2 in the ash of the three prepared biochars.

[0084] (IV) Phase change performance of composite PCM

[0085] The DSC technology is used to accurately test the thermal performance parameters (phase change temperature and latent heat) of MA and its composite phase change materials. The DSC curves of MA and composite phase change materials are shown in Figure 2. Figure 4 (a) and (b) are shown in Table 2. Figure 4 As shown in (a), the upward and downward curves represent the endothermic process and the exothermic process, respectively. The upward peak is the endothermic peak, and the downward peak is the exothermic peak. Pure MA has two phase change peaks, corresponding to the solid-liquid phase change process and the liquid-solid phase change process, respectively. In addition, the DSC curve of the composite phase change material is very similar to that of pure MA. As shown in Table 2, the melting temperature and crystallization temperature of pure myristic acid are 56.86°C and 48.5°C, respectively, and the corresponding melting enthalpy and crystallization enthalpy are 192.7 J / g and 192.2 J / g, respectively, indicating that MA has good phase change behavior and high latent heat. However, compared with pure MA, the latent heat of the composite phase change material is lower, and the results can also be seen from Figure 4(a) and (b) are intuitively obtained. The main reason is that the proportion of MA in the composite phase change material decreases and the supporting material biochar has no phase change properties, so the enthalpy value of the composite phase change material is lower than that of pure MA. When the theoretical loading rate of myristic acid is 63%, the impregnation rates R of BC / MA, KBC1.5 / MA, KBC3 / MA, and KBC1.5 / CNT3 / MA (63) are 59.47%, 56.98%, 59.16%, and 62.69%, respectively, which are lower than the theoretical loading rate. The impregnation rate of KBC1.5 / CNT3 / MA is close to the theoretical loading rate. The main reason is that the strong interaction between MA and the supporting material will produce a constraint effect during the phase change process, thereby limiting the normal movement of the phase change material.

[0086] Table 2 Comparison of thermal properties of MA and composite phase change materials

[0087]

[0088] a T m : Melting temperature, T c : Crystallization temperature, △H m : Melting enthalpy, △Hc: Crystallization enthalpy.

[0089] b R represents the impregnation rate, which is calculated as follows: △Hm and △H m,MA Respectively represent the melting latent heat of the composite phase change material and pure MA.

[0090] When the theoretical loading rate of myristic acid is 75%, the impregnation rates of KBC1.5 / CNT1 / MA(75), KBC1.5 / CNT2 / MA(75), and KBC1.5 / CNT3 / MA(75) are 74.83%, 74.47%, and 73.74%, respectively, which are very close to the theoretical loading rate. In addition, we conducted 100 solid-liquid cycles on the sample KBC1.5 / CNT2 / MA(75) to test the thermal stability of the composite PCMs. The obtained DSC curve is shown in Figure 4 As shown in (c), the 100-time solid-liquid cycle curve is almost identical to the curve before the cycle, and its phase transition temperature and phase transition latent heat do not change significantly, indicating that the prepared sample has good thermal stability.

[0091] In order to evaluate the feasibility of composite phase change materials in practical applications, thermal stability is a crucial consideration. The inventors conducted thermogravimetric analysis on MA / biochar composite phase change materials with constant loading rate to deeply explore the effect of biochar microstructure on the adsorption and stability performance of composite phase change materials. Figure 5 TG curves and DTG curves of biochar and MA / biochar phase change composites. Figure 5As shown in (a), the TG curve of pure MA starts to decrease from about 50℃, decomposes completely at 250℃, and then the weight remains unchanged. The MA / biochar composite phase change material has a slight weight loss in the range of 0-100℃, which is caused by water loss. The TG curve drops rapidly in the range of 200-250℃, which is consistent with the downward trend of pure MA. At 250℃, the weight loss rates of KBC 1.5 / MA(63), KBC3 / MA(63), and KBC1.5 / CNT3 / MA(63) are not much different, which are 63%, 60.94%, and 64.67%, respectively. After 250℃, the weight loss rate slows down and the TG curve shows a slow downward trend. This is because the phase change material loaded in the composite phase change material has almost been completely decomposed by heat, while the three carriers BC, KBC1.5, and KBC3 as the composite phase change material undergo a little decomposition during the subsequent heating process. At the same time, it can be intuitively seen that the modified biochar has a better adsorption effect on MA than the biochar directly carbonized at high temperature.

[0092] (V) Temperature response behavior of composite phase change materials

[0093] In order to further study the temperature regulation ability of different phase change materials, the heat transfer rate of composite PCMs was studied. The temperature of the heating stage was constant at 65°C, and the thickness of the samples was 2.8 mm. The samples were placed on the heating stage, and the images of the transient temperature distribution during the heating process were recorded by an infrared thermal imager. Figure 6As shown in (a), when the theoretical loading rate of myristic acid is 63% and the heating time is 1 min, the instantaneous temperature of the sample exceeds 46°C. As the heating time increases, the surface temperature of sample KBC1.5 / MA / CNT3 / MA(63) is higher than that of the other two samples. At the same time, it can be clearly observed that this sample is the first to undergo a solid-liquid phase transition, followed by the other two samples. When the heating time is 4 min, there is an obvious color change on the surface of the three samples, and the melted volume of MA in sample KBC1.5 / MA / CNT3 / MA(63) accounts for the largest proportion. When the heating time is 5 min, all three samples have completely melted and are in the liquid-sensing thermal energy stage, but the surface temperature of sample KBC1.5 / MA / CNT3 / MA(63) is still higher than that of other samples. From the results, the heat transfer rate of KBC1.5 / MA(63) is slightly higher than that of KBC3 / MA(63), and the heat transfer rate of KBC1.5 / CNT3 / MA(63) after adding CNTs is even higher, and the temperature change is much greater than that of the other two samples. This may be because the addition of carbon nanotubes increases the thermal conductivity of the sample, making the heat conduction faster. Secondly, the shape of the sample remains unchanged during the entire heating process, which shows that the prepared biochar carrier can not only adsorb the phase change material MA well, but also, when MA is heated and melted, through hydrogen bonds and forces, the molten MA flows in the pores of the biochar carrier without causing the sample to leak.

[0094] In order to further explore the potential of biochar carriers in loading MA, the inventors subsequently prepared three phase change samples incorporating carbon nanotubes, and the theoretical MA loading rate of these samples was set to 75%. Figure 6 As shown in (b), it can be observed that the shapes of the three samples remain unchanged during the heating process, and they have good shape stability. The color change of KBC1.5 / CNT2 / MA(75) in the same time period (5min) is the most significant, and the MA in the sample has completely melted, indicating that its heat transfer rate is the highest. The temperature changes of different samples during the heating process and the differences between them. It can be concluded that the addition of CNTs greatly improves the heat transfer rate of the samples. Among the three samples, KBC1.5 / CNT2 / MA(75) has the highest heat transfer rate, which may be because the carbon nanotubes added to this composite material have a more suitable aspect ratio and a higher thermal conductivity.

[0095] (VI) Shape stability of composite phase change materials

[0096] In order to evaluate the shape stability and anti-leakage performance of MA and composite phase change materials, the materials were pressed into sheets and placed in a constant temperature oven to observe their heating anti-leakage performance. Figure 7As shown, pure MA had melted more than half after heating for 10 minutes, and completely melted after heating for 20 minutes. BC / MA(63) collapsed after heating for 10 minutes, and leakage signs appeared around it, indicating that both MA and BC / MA(63) had no shape stability. Compared with MA and BC / MA, KBC1.5 / MA(63) and KBC3 / MA(63) maintained consistent shapes throughout the heating process, with no obvious leakage (the experimental conditions of the KBC1.5 / MA(63) sample were the same as these two samples). In addition Figure 7 The mass loss rate of the composite phase change material heated at 65°C for 20 minutes is shown. The mass loss rate of BC / MA (63) is 8.5%, and the mass loss rate of KBC / MA (63) is reduced to less than 1%. This is mainly due to the rich microporous structure of biochar after KOH activation, its capillary force on myristic acid, and the presence of abundant oxygen-containing functional groups on the surface of biochar. These functional groups show high affinity for MA due to the effect of hydrogen bonds. These forces limit the movement of MA molecular chains and prevent MA leakage.

[0097] When the theoretical loading rate of MA reaches 75%, it can be seen that KBC1.5 / MA(75) also has the same experimental phenomenon as KBC1.5 / MA(63), and collapse occurs after heating for 10 minutes. However, it can be observed that the shape of KBC1.5 / CNT1 / MA(75) with added CNTs remains stable during the entire heating process, but there is a slight leakage after heating for 10 minutes. After heating for 20 minutes, obvious leakage marks have appeared on the filter paper. After subsequent calculation and analysis, the mass loss rates of KBC1.5 / CNT1 / MA(75), KBC1.5 / CNT2 / MA(75), and KBC1.5 / CNT3MA(75) are 1.9%, 2.89%, and 3.95%, respectively, indicating that the addition of carbon nanotubes in the composite phase change material improves the anti-leakage performance of the matrix to the phase change material.

[0098] The sample was pressed into a sheet with a diameter of 2 cm and a thickness of 2.8 mm, and the thermal conductivity of the sample was tested by the Hot Disk method / transient flat plate heat source method using the Hot Disk TPS2500S equipment, as shown in Table 3. As can be seen from Table 3, the thermal conductivity of the original phase change material MA is 0.38 W / (m·K), the thermal conductivity of BC / MA(63) increases to 0.44 W / (m·K), and the thermal conductivity of KBC1.5 / CNT2 / MA(75) with the addition of carbon nanotubes further increases to 0.53 W / (m·K), and the thermal conductivity is increased by 40.1%.

[0099] Table 3 Thermal conductivity test of phase change materials

[0100]

[0101] (VII) Photothermal properties of composite phase change materials

[0102] Photothermal conversion technology shows great potential in the field of solar energy utilization. Phase change materials can effectively convert solar energy into thermal energy and store it. The photothermal conversion efficiency of composite phase change materials directly determines its efficiency in the process of energy conversion and storage, and is a key indicator for measuring material performance. In the present invention, a scientific research xenon lamp (BBZM-1, maximum power 250W) is used as a light source to simulate sunlight, and the radiation intensity is measured by a radiometer to explore the photothermal conversion performance of composite phase change materials. The above-mentioned thin sheet sample is pressed into a thermal insulation layer, and a patch thermocouple is placed at the bottom. Turn on the xenon lamp, and turn on the data acquisition instrument at the same time to record the temperature change at the bottom of the sample at a time interval of 3s to obtain a photothermal conversion curve. The temperature change of the material under illumination conditions is monitored and recorded in real time. This data recording process provides a direct basis for analyzing the photothermal conversion efficiency of the material.

[0103] The photothermal conversion time-temperature curve of biochar / myristic acid phase change composite material is shown in Figure 8 As shown in (a) and (b). In the initial endothermic stage of photothermal conversion, the temperature of the composite material rises rapidly due to the irradiation of the xenon lamp, while the myristic acid loaded in the composite phase change material remains in a solid state. The experiment found that the composite phase change material has good light absorption ability, converts light energy into heat energy and stores it inside the composite phase change material in the form of sensible heat, which accelerates the rate of temperature rise of the composite phase change material and reaches the phase change temperature in a shorter time. When the temperature reaches the melting point of the composite phase change material, a significantly inclined temperature growth platform appears, indicating that the melting process of the composite phase change material occurs at this stage. In this process, myristic acid will transform from solid to liquid, and the energy converted from photothermal to liquid is stored in the form of latent heat. When the melting process is over, the temperature rises rapidly again.

[0104] Depend on Figure 8(a) It can be clearly seen that the temperature of pure MA and BC / MA (63) rises rapidly within 4 minutes of illumination. However, as the illumination time increases, the temperature curve shows a slow upward trend. Finally, due to poor light absorption and poor thermal conductivity, pure MA and BC / MA (63) cannot complete the phase change process under the irradiation of the simulated light source. The thermal properties of KBC1.5 / MA (63) and KBC3 / MA (63) prepared by KOH-modified biochar have been greatly improved, and the phase change process can be successfully completed within the illumination time. In order to further improve the thermal properties of the composite phase change material, the inventor introduced carbon nanomaterials (CNT) into it and prepared the sample KBC1.5 / CNT3 / MA (63). It can be seen from the light-heat conversion curve of the phase change composite material that the phase change time of KBC1.5 / MA (63), KBC3 / MA (63) and KBC1.5 / CNT3 / MA (63) are 321 seconds, 384 seconds and 309 seconds, respectively. After the phase change, the temperature of the three samples increased rapidly under subsequent illumination, but the temperature of KBC1.5 / CNT3 / MA(63) was always higher than the other two samples during the temperature rise process and stabilized before the end of illumination. After 16 minutes of continuous illumination, the light source was turned off and the sample began to release heat. After the temperature dropped rapidly to the crystallization temperature, another inclined temperature platform appeared again, which corresponded to the release of latent heat of the composite phase change material.

[0105] In addition, the inventors prepared three samples of biochar-carbon nanotube composite matrix loaded with 75% MA, and the photothermal conversion curves are shown in FIG. Figure 8 As shown in (b), the three samples completed the solid-liquid phase transition and latent heat release of myristic acid in the samples during the illumination and cooling stages. The phase transition times of KBC1.5 / CNT1 / MA(75), KBC1.5 / CNT2 / MA(75), and KBC1.5 / CNT3 / MA(75) were 320 seconds, 302 seconds, and 368 seconds, respectively.

[0106] The photothermal conversion efficiency of MA and composite PCMs can be calculated according to formula (1):

[0107]

[0108] Where m is the mass of the sample, ΔH is the phase change enthalpy of the sample, P is the light intensity, A is the area of ​​the sample receiving light, and Δt is the phase change time of the sample

[0109] Based on equation (1), the solar thermal storage efficiency of the composite PCM is Figure 8As shown. Pure MA and KBC / MA (63) show poor light absorption capacity in the unfinished melting process. Therefore, its solar-thermal storage efficiency is 0. The light-to-heat conversion efficiency of KBC1.5 / MA and KBC3 / MA composite phase change materials are 58.88% and 51.11% respectively, and the light-to-heat conversion efficiency of KBC1.5 / CNT3 / MA (63) phase change material with added carbon nanotubes reaches 67.26%. When the theoretical loading rate of MA is increased to 75%, the light-to-heat conversion efficiency of the three samples KBC1.5 / CNT1 / MA (75), KBC1.5 / CNT2 / MA (75), and KBC1.5 / CNT3 / MA (75) are 71.72%, 73.67%, and 61.92% respectively. The present invention shows that under the influence of modified BC and CNTs, the light absorption capacity and thermal conductivity of the composite phase change material are qualitatively improved compared with pure MA. This demonstrates the great potential of the composite phase change material prepared by the present invention in the field of solar thermal conversion and storage.

[0110] In summary, in the present invention, a composite phase change material was prepared by modifying biochar, doping carbon nanotubes, and loading MA. Various aspects of the composite PCMs were studied, mainly including microstructure, packaging performance, thermal performance, and light-to-heat conversion capability. The main conclusions are as follows:

[0111] (1) The surface area and pore volume of biochar after KOH modification were greatly improved, and the specific surface area of ​​KBC3 reached 813.56 m 2 / g, the large specific surface area, rich pore volume and surface functional groups greatly improved its adsorption performance, thereby increasing the loading capacity of biochar for MA (increased to 63%). Various characterization results show that the MA sample was successfully loaded into the porous material and the structure remained intact. Compared with MA, the thermal conductivity of KBC1.5 / CNT2 / MA(75) increased by 40.1%.

[0112] (2) KBC modification can significantly improve the anti-leakage ability of composite phase change materials. The mass loss rate of KBC1.5 / MA(63) during the shape stability test was less than 1%. When the loading rate of MA was increased to 75%, KBC1.5 / MA(75) leaked seriously during the phase change process, and the mass loss rate reached 8.5%. However, only a small amount of leakage occurred during the thermal stability test of KBC1.5 / CNT1 / MA(75), and the anti-leakage ability was greatly enhanced. In addition, KBC1.5 / CNT2 / MA(75) has a higher phase change enthalpy value of 143.5J / g (75.1% of 11MA). After 100 heating and cooling cycle experiments, its DSC curve coincided with the single curve, showing good stability.

[0113] (3) BC modification and the introduction of CNTs greatly improved the thermal conductivity and photothermal conversion capacity of the composite PCMs. The photothermal conversion rate of pure MA and BC / MA (63) was 0. The photothermal conversion rate of KBC1.5 / MA increased to 58.88%, while the photothermal conversion rate of KBC1.5 / CNT2 / MA (63) further increased to 76.37%. The addition of a small amount of CNTs has an important influence on the performance improvement of composite PCMs. This is mainly because carbon nanotubes have a high thermal conductivity, which improves the thermal conductivity and heat transfer rate of the sample. At the same time, their suitable aspect ratio can greatly improve the sample's light absorption capacity for visible light.

Claims

1. A method for preparing a biochar / carbon nanotube / myristic acid composite phase change material, characterized in that: The method specifically comprises the following steps: (1) Preparation of biochar / myristic acid Myristic acid (MA) and anhydrous ethanol are mixed, heated and melted to obtain a liquid phase change material; biochar (BC) is then added to the liquid phase change material according to a ratio and mixed; the obtained mixture is then vacuum impregnated, and after the vacuum impregnation is completed, the biochar / myristic acid (BC / MA) is obtained; (2) Preparation of biochar / carbon nanotubes / myristic acid Carbon nanotubes (CNTs) are added to molten myristic acid according to a ratio, and then stirred and ultrasonicated under molten conditions to obtain a carbon nanotube / myristic acid (MA / CNTs) mixed solution; KOH-activated biochar (KBC) is then added to the MA / CNTs mixed solution, mixed evenly, and the obtained mixture is vacuum dried to obtain the biochar / carbon nanotube / myristic acid composite phase change material.

2. The preparation method according to claim 1, characterized in that: The mass ratio of myristic acid to biochar in step (1) is 1:1 to 2:

1.

3. The preparation method according to claim 1, characterized in that: The preparation method of the biochar in step (1) is as follows: The dried plant straw is crushed and placed in a tubular furnace, and heated to 500-700° C. for pyrolysis for 1-3 hours under the protection of an inert gas; after the pyrolysis is completed, the obtained product is ground to obtain the biochar.

4. The preparation method according to claim 1, characterized in that: The mass ratio of the carbon nanotubes to myristic acid in step (2) is 1:10 to 1:

30.

5. The preparation method according to claim 1, characterized in that: The activated biochar in step (2) is prepared by the following method: (A) dissolving KOH in deionized water according to a ratio to obtain a KOH solution; then adding plant straw particles to the KOH solution, immersing for 20-30 hours, filtering, and drying to obtain KOH-activated plant straw; (B) placing the KOH-activated plant straw in a tubular furnace, heating it to 500-700° C. for pyrolysis for 1-3 hours under the protection of an inert gas; after the pyrolysis is completed, washing the obtained product to neutrality, drying, and grinding to obtain KOH-activated biochar.

6. The preparation method according to claim 5, characterized in that: In step (A), the mass ratio of KOH to plant straw particles is (1-3):

1.

7. The preparation method according to claim 6, characterized in that: In step (A), the mass ratio of KOH to plant straw particles is 1.5:

1.

8. The biochar / carbon nanotube / myristic acid composite phase change material prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the biochar / carbon nanotube / myristic acid composite phase change material prepared by the preparation method according to any one of claims 1 to 7 as a photothermal conversion material.

10. A photothermal conversion material, characterized in that: The invention comprises a biochar / carbon nanotube / myristic acid composite phase change material prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Light / electricity-heat conversion composite phase change material with high thermal conductivity and preparation method of light / electricity-heat conversion composite phase change material

    CN117106419A

  • Preparation method and application of charcoal-based shaped composite phase change energy storage material

    CN118185574A

Cited By

  • Hydrothermally modified wood-based photo-thermal super-hydrophobic composite phase change heat storage material as well as preparation method and application thereof

    CN121592312A

  • A hydrothermally modified wood-based photo-thermal super-hydrophobic composite phase change heat storage material, a preparation method and application thereof

    CN121592312B

  • Bamboo-based photo-thermal super-hydrophobic phase change composite material as well as preparation method and application thereof

    CN121610249A